La sexualidad femenina en términos de oppressión y liberación por medio del sexo - Rodriguez, Nereida Perdigon, author; Leal, Francisco, advisor; Pedrós-Gascón, Antonio, committee member; López-Cabrales, María del Mar, 1967-, committee member; Martey, Rosa Mikeal, committee member (Colorado State University. Libraries, 2010)
This work studies femenine sexuality in terms of oppression and the liberation of female characters from three novels: Las edades de Lulú, (1989) de Almudena Grandes, La nada cotidiana, (1995) de Zoé Valdés y La casa de los espíritu, de Isabel Allende, (1982). This investigation wants to state women's sexual evolution, as well as the responsibility that they have to build the change from an object to an active sexual subject. This thesis is not meant to show that the feminine characters in these novels have been free of masculine oppression, but it is very important to emphasize that these women have been making progress and winning battles in the context of their own lives, becoming the heroines in their societies. I want to show through this research that women have been victims in society, but also, throughout their stories have destroyed the victim's dress to become the leaders of their own lives.
Female sexuality in terms of oppression and liberation through sex
Department Head: Paola Malpezzi Price.
Text in Spanish; title and abstract in English and Spanish.